2014
DOI: 10.1371/journal.pone.0084221
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of Intestinal SREBP2 in Mice Increases Serum Cholesterol

Abstract: Sterol Response Element Binding Protein 2 (SREBP2) transcription factor is a master regulator of cholesterol homeostasis. Treatment with statins, inhibitors of cholesterol synthesis, activates intestinal SREBP2, which may hinder their cholesterol-lowering effects. Overactivation of SREBP2 in mouse liver was shown to have no effect on plasma cholesterol. However, the influence of activating intestinal SREBP2 on plasma cholesterol is not known. We have generated a novel transgenic mouse model with intestine spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…We observed signifi cant increases in the amount of intestinal nuclear SREBPs and cholesterol synthesis, such that synthesis in the intestine exceeded that in liver on an organ-by-organ basis ( 14 ). Similar results were found when truncated SREBP-2 was expressed in intestinal epithelia ( 15 ). These results indicated that Insig proteins mediate feedback inhibition of cholesterol synthesis in the intestine and suggested that Scap, the binding partner for Insig, also likely plays a role in SREBP processing in the intestine.…”
Section: Quantitative Real-time Rt-pcrsupporting
confidence: 83%
“…We observed signifi cant increases in the amount of intestinal nuclear SREBPs and cholesterol synthesis, such that synthesis in the intestine exceeded that in liver on an organ-by-organ basis ( 14 ). Similar results were found when truncated SREBP-2 was expressed in intestinal epithelia ( 15 ). These results indicated that Insig proteins mediate feedback inhibition of cholesterol synthesis in the intestine and suggested that Scap, the binding partner for Insig, also likely plays a role in SREBP processing in the intestine.…”
Section: Quantitative Real-time Rt-pcrsupporting
confidence: 83%
“…SREBP-1 governs fatty acid and triacylglyceride metabolism ( Guo et al, 2014 ; Bitter et al, 2015 ). In contrast, SREBP-2 is deeply involved in the regulation of cholesterol metabolism ( Ma et al, 2014 ) Reflecting such differences in biological function, the transcript for SREBP-1, which is most abundant in the liver and adrenal gland, has a shorter acidic activation domain, and the protein acts selectively to increase the mRNAs for enzymes involved in fatty acids synthesis ( Soyal et al, 2015 ). In contrast, the ubiquitously expressed SREBP-2 transcript has a long activation domain.…”
Section: Discussionmentioning
confidence: 99%
“…The underpinning reason for the discrepancy is not known, but immunofluorescence analysis for VSVG-LPA 2 expression showed that the expression levels of TG LPA 2 is about two-fold greater in the small intestine. Villin promoter activity and its expression are greater in the small intestine than in colon [ 26 , 27 ]. LPA is known to regulate actin cytoskeletal dynamics, which is closely associated with cell division [ 28 ].…”
Section: Discussionmentioning
confidence: 99%